Exploring the antioxidant and protective effects of Marsdenia thyrsiflora Hook.f. leaf extract against carbon tetrachloride-induced hepatic damage in rat models - Saha, Sushmita; Alshammari, Abdulrahman; Albekairi, Norah A.; Zulfiquar, Tasniya Nahiyan; Shakil, Md Salman; Mondal, Kakoli Rani; Kundu, Milton Kumar; Mondal, Milon; Mubarak, Mohammad S. (Frontiers in Pharmacology, 2024)
Introduction Medicinal plants are vital to healthcare, yet many remain unexplored. Marsdenia thyrsiflora Hook.f., from Bangladesh’s Bhawal Forest, lacks research on its medicinal properties, especially its antioxidant capacities and protection against CCl4-induced liver toxicity. This study aims to evaluate the antioxidant properties of M. thyrsiflora leaf extract to determine its protective effects on rodents against CCl4-induced liver injury. Methods After extraction, the total phenol, flavonoid content, and antioxidant capacity of the leaf extract were measured using established protocols. Free radical scavenging abilities were evaluated with 2,2′-diphenyl-1-picrylhydrazyl (DPPH), nitric oxide (NO) assays. Additionally, reducing power was assessed through cupric-reducing and ferric-reducing assays. Based on the OECD 420 recommendation, acute toxicity was tested on Swiss albino mice to establish an effective and safe dosage. For the hepatoprotective study, Sprague-Dawley rats were pre-treated with M. thyrsiflora leaf methanolic extract (MTLM) at 250 and 500 mg/kg body weight, and CCl4 was administered to induce liver damage. Serum hepatic enzyme levels (alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT)), lipid profile (total cholesterol, triglycerides), total bilirubin, and markers of lipid peroxidation (Malondialdehyde (MDA)) were measured. The activities of antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH) were also evaluated to assess oxidative stress. Results The results demonstrated that MTLM, rich in phenolic and flavonoid content, exhibits significant antioxidant activities in DPPH and NO radical scavenging assays, as well as in reducing power assays. The acute toxicity study confirmed the safety of MTLM, with no adverse effects observed even at high doses. For the hepatoprotective study, rats were administered CCl4 to induce liver damage, followed by treatment with MTLM. Results showed that MTLM significantly reduces liver damage markers such as elevated serum hepatic enzyme levels, lipid profile, total bilirubin, and lipid peroxidation and improves the activities of GSH and key antioxidant enzymes such as SOD and CAT. Histopathological analysis corroborated these findings, displaying reduced necrosis, inflammation, and edema in liver tissues treated with MTLM. Conclusion MTLM extract exhibits potent antioxidant and hepatoprotective properties. Its ability to attenuate oxidative stress, enhance antioxidant enzyme activities, and facilitate histopathological changes in the liver highlights its potential as a natural therapeutic agent for liver damage. However, further investigation is required to understand its molecular processes, safety profiles, and active component characterization.